Strategi Penguatan Branding dan Digital Marketing UMKM Tape Ketan di Desa Mondoteko melalui Media Sosial dan Inovasi Kemasan - Faizatul Ulya; Shania Nur Afifah; Sofi Duwi Handayani; Nur Listiani (FKIP, Universitas Palangka Raya, 2026)
This community service activity aimed to strengthen the branding and improve the digital marketing capacity of the Tape Ketan MSME in Mondoteko Village through the utilization of social media and packaging innovation. The business partner faced several major problems, including weak business visual identity, limited use of social media as a promotional tool, and simple product packaging designs that were less attractive to consumers. These conditions resulted in low product appeal and limited marketing reach. The implementation method used a participatory approach through direct assistance to business owners. The activity stages included initial observation, identification of partner needs, design of promotional banners, creation and optimization of social media accounts, and redesign of product packaging to make it more modern, informative, and marketable. In addition, MSME owners were educated about the importance of branding, digital marketing strategies, and consistency in building a business image. The results showed an increase in the understanding and skills of MSME owners in utilizing digital media for promotion. Product packaging became more attractive and professional, while the use of social media became more active and organized. These improvements had a positive impact on increasing consumer interest, expanding market reach, and enhancing the competitiveness of MSMEs in a sustainable manner.